Contaminated water treatment with Activated charcoal build from cocoa pod husk. Issue 1 (April 2021) - Sadheesh, S; Shankar, R; Santhosh Kumar, S; Guru Prasath, B
Abstract: In this world, effluents released from the refinery affect the environment at major as different studies says that the natural agents have high capacity to absorb bivalent metal ions. Cocoa pod husk is widely produced in south India in minimum cost. During this study, the metal such as lead and copper was investigated. The cocoa pod husk is carbonized at five hundred degree Celsius and saturated with one molar hydrochloric acid at seven hundred degree Celsius in muffle furnace for two hours (atomic number-6). The final product is allowed to test by adsorbing the metals such as lead and copper to make different pH, dosage and contact time. The capacity to adsorb and metal removal percentage were documented when the contact time reaching two hours. The efficiency of the adsorbent to remove the heavy metal lead and copper was 78 % and 97% respectively.